Interactions between surrounding landscape biodiversity and intermittent rivers in mediterranean environments – case study of the Caia River - Kaletovà, Tatiana (2022)
Landscape is a dynamic mosaic of various structures interacting together. Neglecting or overusing one part of this mosaic may boost up or damage the development of others. For instance, overgrazing may increase soil erosion process which may clog a river/stream. In this regard land use changes, climate change and landscape management may lead to increase the intermittency of the surface watercourses, as well as in the ecosystem services provided by riverscapes for humans. Therefore, the present research focus on the existing interactions between the Caia River, an intermittent river located in the Mediterranean region, and its surrounding agricultural and natural landscapes. The performed analyses considered the identification of the existing interaction between natural and agricultural landscapes with the Caia River defining the predictable ecosystem services provided by each element of the landscape and assessing the potential decrease of the ecosystem services provided in case of landscape changes, which according to the performed research might enclose significant impacts both in ecologic and socioeconomic terms.